Extended schooling and community education: mapping the policy terrain (UCL Press, 2013)
New Labour's extended schools initiative added to existing models of community schooling. The paper identifies the key principles behind extended schooling, making comparisons with historical models and contemporary trends in community education. Part one examines New Labour's use of extended schools to deliver their social policy agenda. Part two focuses on alternative models of community schooling used in England and Scotland, suggesting alternative solutions to issues of social disadvantage and educational underachievement. Part three examines the European tradition of social pedagogy exploring the potential contributions it brings to educational and welfare practice in England given the new Government's approach to localism and the 'Big Society'.